The technical efficiency of secondary schools in the Pardubice Region - Provazníková, Romana; Chlebounová, Denisa (Univerzita Pardubice, 2018)
This contribution deals with capacity of secondary schools in the context of technical efficiency. The Czech education suffers from insufficient use of secondary but also primary school capacities. The aim of this paper is to evaluate technical efficiency of vocational secondary schools in the Pardubice region with the focus on their capacities, and that in relation to the actual number of pupils for the school year of 2016/2017. Data Envelopment Analysis (DEA) was used to meet this goal. Two inputs were selected – the number of classes and the expenditure on teacher salaries, and one output – actual number of pupils. The results of this analysis show that five vocational secondary schools from the 20 examined vocational secondary schools use effectively their capacities. The optimal utilization of capacities calculated as quotient of actual number of pupils and optimal number of pupils expresses the fact that the examined schools use their capacities on average only at 60 % - only three schools use their capacities above 80 %. This situation is caused by a long-term decline in birth rates when the number of secondary school pupils is decreasing.
Technická efektivnost středních škol v Pardubickém kraji
Keywords: data envelopment analysis; secondary schools; capacity; technical efficiency; number of pupils; analýza datových obalů; střední školy; kapacita; technická efektivnost; počet žáků